Digital Capitalism and Distributive Forces (excerpt) - Pfeiffer, Sabine (Journal of Economic Sociology, 2024)
In her book Digital Capitalism and Distributive Forces, sociology professor Sabina Pfeiffer questions the idea that digitalization is a technology that replaces human labor. In her analysis of the novelties brought by digitalization and digital capitalism, the author introduces the concept of distributive powers by analogy with Marx’s concept of productive power. Pfeiffer shows that digital capitalism is aimed not so much at the efficient production of value, but rather at its rapid, risk-free and permanently guaranteed implementation in the markets. Studying this dynamic and its consequences also leads to the question of how destructive the distributional forces of digital capitalism can be. The Journal of Economic Sociology publishes an Introduction where Pfeiffer formulates the main assumption, which she develops on a theoretical and empirical level in the presented book. The hypothesis is related to the problem of modern capitalism, where economic value is provided only by successful sales. Additionally, Pfeiffer discusses what constitutes the novelty of digital capitalism and what its immanent diagnoses are. Finally, the author provides a detailed overview of the book’s structure and its main ideas.